Suicides in Nunavik: a life course study - Affleck, William (Int J Circumpolar Health, 2021)
This study reports results of a life course study conducted with Inuit in Nunavik to obtain information on the life adversities and cumulative burden of adversity for three groups: those who died by suicide, those who attempted suicide, and those who experienced suicidal ideation but never attempted. The study involved different levels of collaboration between health authorities, front-line health workers and the research team. Results indicate that substance misuse and relational difficulties are most associated with the burden of adversity for those people who died by suicide, while bullying is most associated with the burden of adversity for those people who have made suicide attempts and those who have never made a suicide attempt. Specifically targeting parent–child relations, substance misuse, and bullying may be an important upstream strategy for reducing future suicidality in Nunavik.